High Visceral Adipose Tissue Density Correlates With Unfavorable Outcomes in Patients With Intermediate-Stage Hepatocellular Carcinoma Undergoing Transarterial Chemoembolization - Li, Qiang; Zhang, Lei; Hou, Zhong-Heng; Zhao, Dong-Xu; Li, Jian-Bin; Zhang, Shuai; Yin, Yu; Ni, Cai-Fang; Chen, Tao (Frontiers in Cell and Developmental Biology, 2021)
Objectives: This study aimed to evaluate the association between different body composition features with prognostic outcomes of intermediate stage hepatocellular carcinoma (HCC) patients treated with transarterial chemoembolization (TACE). Methods: The areas and density of skeletal muscle area (SM) and adipose tissue (subcutaneous, SAT; visceral, VAT) were calculated on the pre-TACE CT scans. Overall survival (OS) and progression-free survival (PFS) curves were calculated using the Kaplan-Meier method and compared by log-rank test. The discrimination and performance of body composition features were measured by area under time-dependent receiver operating characteristic (ROC) curve. Univariate and multivariate Cox proportional hazard analyses were applied to identify the association between body composition parameters and outcomes. Results: A significant prolonged OS and PFS was displayed by Kaplan-Meier curve analysis for HCC patients with VAT HU below -89.1 (25.1 months, 95%CI:18.1-32.1 vs. 17.6 months, 95%CI:16.3-18.8, P<0.0001, 15.4 months, 95%CI:10.6-20.2 vs. 6.6 months, 95%CI:4.9-8.3, P<0.0001, respectively). The 1-year, 2-year, 3-year and 5-year OS area under the curve (AUC) values of the VAT HU were higher than the other body composition parameters. Meanwhile, it is also found that 3-month, 6-month, 9-month and 12-month PFS AUC values of VAT HU were the highest among all the parameters. Univariate and multivariate Cox-regression analysis suggested that a significant association between VAT density and outcomes (OS, HR: 1.015, 95% CI:1.004-1.025, P=0.005, PFS, HR:1.026, 95%CI: 1.016-1.036, P <0.0001, respectively). Conclusions: The VAT density could provide prognostic prediction value and maybe helpful to stratify the intermediate stage HCC patients.